MDA5 Induces a Stronger Interferon Response than RIG-I to GCRV Infection through a Mechanism Involving the Phosphorylation and Dimerization of IRF3 and IRF7 in CIK Cells - Wan, Quanyuan; Yang, Chunrong; Rao, Youliang; Liao, Zhiwei; Su, Jianguo (Frontiers in Immunology, 2017)
Retinoic acid-inducible gene I (RIG-I) and melanoma differentiation associated gene 5 (MDA5) are critical cytosolic sensors that trigger the production of interferons (IFNs). Though their recognition functions are well identified, their unique roles in the downstream signal transduction remain to be elucidated. Herein, we report the differential effect between grass carp (Ctenopharyngodon idella) MDA5 (CiMDA5) and CiRIG-I on the production of various IFNs upon grass carp reovirus (GCRV) infection in C. idella kidney (CIK) cell line. In CIK cells, grass carp IFN1 (CiIFN1) and CiIFN3 are relatively highly expressed while CiIFN2 and CiIFN4 are relatively slightly expressed. Following GCRV infection, CiMDA5 induces a more extensive type I IFN response than CiRIG-I. Further investigation reveals that both CiMDA5 and CiRIG-I facilitate the expression and total phosphorylation levels of grass carp IFN regulatory factor (IRF) 3 (CiIRF3) and CiIRF7 upon GCRV infection or poly(I:C) sitimulation. However, the difference is that CiRIG-I decreases the threonine phosphorylation level of CiIRF7. As a consequence, CiMDA5 enhances the heterodimerization of CiIRF3 and CiIRF7, and homodimerization of CiIRF7; whereas CiRIG-I facilitates the heterodimerization but attenuates homodimerization of CiIRF7. Moreover, the present study suggests that CiIRF3 and CiIRF7 heterodimers and CiIRF7 homodimers are able to induce more extensive IFN-I responses than CiIRF3 homodimers under GCRV infection. Additionally, CiMDA5 induces a stronger type II IFN (IFN-II) response against GCRV infection than CiRIG-I. Collectively, these results demonstrate that CiMDA5 plays a more potent role than CiRIG-I in IFN response to GCRV infection through differentially regulating the phosphorylation and dimerization of CiIRF3 and CiIRF7.